Capacity Allocation Method for Wind-Solar-Hydro-Storage Complementary System Considering Time and Spatial Transfer Characteristics of Load - Jie WEN; Jichun LIU; Zhengnan WEN; Jianhua LI; Chenxin LI (Zhongguo dianli)
By taking advantage of the quick regulation ability of cascade hydropower and the flexible conversion of the working conditions between power generation and pumping of the pumping generator units, and on the basis of compensating the fluctuation and uncontrollability of wind and PV output, a wind-solar-hydro-storage complementary system model is established at the source end to enhance the regulation ability of the power generation system. At the same time, considering the market spot electricity price and the time and spatial transfer characteristics of load, a load-side model is established, and a source-grid-load interaction strategy is proposed based on multiple system indicators such as the economy and state evenness of system and the load tracking, with consideration of the randomness of wind/solar power output at source end and the system network constraints. Based on above study results, a multi-objective capacity allocation model of complementary power generation system is built. Finally, through a case simulation, the nonlinear optimization problem is solved by professional optimization software (LINGO), and the allocation capacities of the source end system under different planning years and scenarios are obtained, which has verified the effectiveness of the proposed method in improving the system indicators.